Instituto Federal do Amapá no processo de expansão da educação superior pública amapaense (2011 a 2018) - OLIVEIRA, Júlia Milena da Paixão (UNIFAP – Universidade Federal do Amapá, 2022)
This thesis discusses the topic higher education policies and its aim is to study the higher education expansion by offering undergraduate courses at Federal Institutes. The general objective consists in analyze the participation of the Federal Institute of Amapá (Ifap) in the process of public higher education expansion in Amapá, from 2011 to 2018, with emphasis on the categories academic units, teaching and administrative staff, courses, vacancies and enrollments. As theoretical-methodological basis it is present the dialectical and historical materialism, since it is understandable that the higher education expansion through Federal Institutes is not a neutral and/or isolated phenomenon, but part of an amount of social relations driven by the dominant groups interests, which is also surrounded by controversy and, although it is not the main aim, they attend some social demands. Methodologically, it is a desk research, with quanti-qualitative approach. The research was conducted on the basis of documents data that shows the expansion of the Brazilian higher education in national, regional and local levels. It was analyzed Higher Education Census and official documents from the Federal Institute of Amapá (Ifap), as Institutional Development Plan (PDI) and management registers. The results highlight that Ifap contributed, from 2011 to 2018, offering 2.160 vacancies, distributed for 14 on-site courses, and 550 vacancies distributed in 2 distance learning courses. Ifap was the second public institute with the largest number of courses, only to Unifap that offered 63,4% of the undergraduate courses in Amapá. Documents from Ifap indicate that the undergraduate courses were created from the subjects offered in the general education of the technical courses at middle school levels, besides being constituted in legal requirement at Federal Institutes, they attend a social demand due to the lack of teachers to work in the basic and higher education area. On the other hand, the other courses, specially the Technology Degree Coursers, were created from the technical training subjects taught at technical courses at middle school level and were justified by the lack of professionals with academic degree to work in areas with potential for the market development. The undergraduate courses enrollments from Ifap presented 745,6% growth at the time researched and in 2018 they represented 9,2% of the enrollments from the public Higher Education Institutes of Amapá. It was also shown that the courses, vacancies and enrollments are still centralised at the Macapá campus, the capital of the state, which has been limiting the process of internalization. In conclusion, the Institute has been reinforcing the undergraduate courses offering, specially the on-site ones, and has significantly contributed to the process of the higher education expansion in Amapá. Even in the face of hardship, Ifap has assumed the commitment of offering higher education and it has shown some concerns in foster improvements for this level of education.